2019
DOI: 10.1021/acs.est.9b03091
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Nontarget Analysis for the Molecular Reconstruction of Organic Aerosol Composition from Glacier Ice Cores

Abstract: Ice cores are climate archives suitable for the reconstruction of past atmospheric composition changes. Ice core analysis provides valuable insight into the chemical nature of aerosols and enables constraining emission inventories of primary emissions and of gas-phase precursors. Changes in the emissions of volatile organic compounds (VOCs) can affect formation rates and mechanisms as well as chemical composition of aerosols during the pre-industrial era, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Steps toward understanding future impacts of ice-sheet OM Ice core OM biogeochemistry is gaining more attention, using C characterization techniques commonly applied for aquatic and terrestrial ecosystems globally (Grannas and others, 2006;D'Andrilli and others, 2017b;Brogi and others, 2018;Xu and others, 2018;Vogel and others, 2019) and newly engineered systems designed for astrobiological research (Malaska and others, 2020). Engineering these techniques for flow through capabilities and/or in situ detection will advance ice core CFA measurements of C quality and quantity at high temporal resolution.…”
Section: Correlations Using Mean Air Surface Temperatures Across Modern Arctic Ice Coresmentioning
confidence: 99%
“…Steps toward understanding future impacts of ice-sheet OM Ice core OM biogeochemistry is gaining more attention, using C characterization techniques commonly applied for aquatic and terrestrial ecosystems globally (Grannas and others, 2006;D'Andrilli and others, 2017b;Brogi and others, 2018;Xu and others, 2018;Vogel and others, 2019) and newly engineered systems designed for astrobiological research (Malaska and others, 2020). Engineering these techniques for flow through capabilities and/or in situ detection will advance ice core CFA measurements of C quality and quantity at high temporal resolution.…”
Section: Correlations Using Mean Air Surface Temperatures Across Modern Arctic Ice Coresmentioning
confidence: 99%
“…On the basis of MS 2 −spectra and retention time, we are able to unambiguously identify CHOn compounds as oxidation products of certain biogenic VOCs. 26 Moreover, low temperatures during winter may lead to lower evaporation of anthropogenic CHOn compounds. A clear decrease of CHOn with short retention times was observed for the winter season, similar to the trend for CHOS compounds (e.g., isopreneorganosulfates (OSs)), which contribute up to 30% of the total intensity in summer.…”
Section: Resultsmentioning
confidence: 99%
“…We also found the homologues of C n H 2n SO 5 (n = 4−17) and C n H 2n SO 6 (n = 4− 16) appearing in the diagram at H/C = 2; such aliphatic OSs were reported as products from the reaction of SO 2 with emissions from liquid fossil fuel. 12,26,60 However, there are also plenty of very polar OSs with extremely short retention times (Figure S5A); most of these have less than 10 carbon atoms (Figure S10B). In this range, one can expect OSs from biogenic emissions; for example, we find C 5 H 8 SO 7 that has been reported as an isoprene-derived organosulfate, 71,72 while C 6 H 10 SO 6 and C 6 H 10 SO 7 have been reported as OSs formed from the OH-initiated oxidation from green leaf volatiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies examined the exhaust of aircraft and found dependencies between particle emissions, their chemical composition, engine design, and the engine operating state. It is stated that the volatile organic fraction of the emitted particles is increasing through photochemical ageing (Kılıç et al, 2018), and the oxidized organic fraction tends to condense on nucleation-mode particles (Wey et al, 2007;Yu et al, 2017). The non-volatile fraction is dominated by black carbon.…”
Section: Introductionmentioning
confidence: 99%